A Practitioner Handbook on Evaluation - Stockmann, Reinhard; Bartley, Gareth (Edward Elgar, 2011)
This comprehensive handbook serves as a reference manual providing answers to virtually every conceivable question that can arise during the planning and implementation process of an evaluation. Offers a basic introduction to the foundations and benefits of this type of investigation, as well as a comparison of different evaluation approaches. Also provides an in-depth methodological framework for data measurement, data collection and data management with a description of the reporting process.